2019
DOI: 10.1212/wnl.0000000000007075
|View full text |Cite
|
Sign up to set email alerts
|

Relative preservation of facial expression recognition in posterior cortical atrophy

Abstract: ObjectiveTo compare recognition of facial expression (FE) vs recognition of facial identity (FI) in posterior cortical atrophy (PCA), with the hypothesis that FE recognition would be relatively preserved in PCA.MethodsIn this observational study, FI and expression recognition tasks were performed by 194 participants in 4 groups, including 39 with Alzheimer disease (AD) (non-PCA), 49 with behavioral variant frontotemporal dementia (bvFTD), 15 with PCA, and 91 healthy controls. Between-group differences in test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The study has some limitations. In terms of the clinical/cognitive assessment, some cognitive functions were only computed as binary variables (impaired/unimpaired) and some more ventral functions were not systematically explored, such as the facial identification (Pressman et al., 2019). Furthermore, not all patients underwent the FDG-PET scan, which lead to a small sample size for that specific analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The study has some limitations. In terms of the clinical/cognitive assessment, some cognitive functions were only computed as binary variables (impaired/unimpaired) and some more ventral functions were not systematically explored, such as the facial identification (Pressman et al., 2019). Furthermore, not all patients underwent the FDG-PET scan, which lead to a small sample size for that specific analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies demonstrate that PCA-focused investigations can shed light on the importance of visual networks to behavior and general visual brain functions. First, a study by Pressman and colleagues [8] revealed relative preservation of facial expression versus facial identification in PCA compared to both typical AD and the behavioral variant of frontotemporal dementia. The authors postulated that these findings could account for the frequent observation of preserved social and emotional functions in PCA and support theories that the origins of 'affective blindsight' (i.e.…”
Section: Posterior Cortical Deficits In Pcamentioning
confidence: 99%